Peran Kepuasan Nasabah sebagai Mediasi E-Servqual terhadap Loyalitas Nasabah pada Bank Sultra Capem Batauga - Muhammad Iqbal Sahlan; Patwayati Patwayati; La Hatani (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to examine and elaborate on the role of user satisfaction as an intervening mechanism in the causal relationship between electronic service quality and customer loyalty at Bank Sultra Capem Batauga. The research design is developed based on a quantitative paradigm employing a cross-sectional survey approach for data collection. Data were obtained through measurement instruments in the form of structured questionnaires. The study population comprises all customers who utilize the digital transaction facilities of Bank Sultra Capem Batauga’s mobile banking services. The sample size was determined using the Slovin formula, resulting in a total of 97 respondents. Data analysis for hypothesis testing was conducted using the Partial Least Squares (PLS) method. The findings indicate that electronic service quality exerts a positive and significant effect on both customer satisfaction and customer loyalty. Furthermore, customer satisfaction was found to have a positive and significant influence on customer loyalty. Finally, the analysis confirms that customer satisfaction serves as a partial mediator in the relationship between electronic service quality and customer loyalty. Thus, customer satisfaction is significantly influenced by electronic service quality and, in turn, significantly enhances customer loyalty, while electronic service quality also demonstrates a direct and significant contribution to customer loyalty.